Membangun Ekonomi Hijau Berbasis UMKM: Peran Mediasi Inovasi Bisnis dalam Implementasi Artificial Intelligence dan Green Technology - Dadang Heri Kusumah; Ahmad Gunawan; Widiyanti Widiyanti; Marcellawati Cecar (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2026)
Low operational efficiency and high environmental impact are the main challenges for MSMEs in Indonesia, especially in West Java. The lack of adoption of Artificial Intelligence (AI) and Green Technology exacerbates this condition, even though MSMEs contribute more than 60% to the national GDP and are the largest absorbers of labor. This research aims to examine the role of business innovation as a mediating variable in optimizing AI and Green Technology to improve the sustainability of the green economy in MSMEs. The quantitative approach was used through a survey with a questionnaire to 400 MSME actors in several regions of West Java, including Bekasi, Bandung, and Cirebon. The sampling techniques applied are proportional area random sampling and purposive sampling. The data was analyzed using the Structural Equation Modelling (SEM) method using SmartPLS 3.0 to test the relationships between variables. The results of the research are expected to make a theoretical and practical contribution in accelerating the transformation of MSMEs towards a technology-based green economy, as well as being a reference for stakeholders in formulating sustainable MSME development strategies.